10.33 SCIENCE AND ENLIGHTENMENT IN PERSONAL SOCIALIZATION - Ramatov Jumaniyaz Sultanovich. TDTr.U is the head of the "Social Sciences" department. Doctor of Philosophy, Professor. Salimov Bakhriddin Lutfullaevich. Associate Professor of TDTr.U. Nurullaev Ziyodilla Sa’dullayevich. Student of TDTr.U. (Innovative technologies in construction Scientific Journal, 2024)
Over the centuries, the noble qualities of our people, such as high spirituality, justice, and enlightenment, have been developed in an integral connection with Eastern philosophy and the teachings of Islam. However, during the 70 years of the last century, the totalitarian ideological oppression based on the intellectually "revolutionary" philosophy, which completely destroyed the spirituality of our people and tried to put the spiritual progress of humanity in a completely opposite direction, was tried to be instilled in the minds of several generations through cruel repressions. This article talks about scientific solutions to the above problem. Key words: religion, worldview, faith, science, Islam, spirituality, education, science. The political independence achieved 28 years ago gave back to our nation the opportunity to freely study and practice our original values. Now our task is to restore our ancient and stable traditions in accordance with the completely new conditions of the present time, and to make our contribution to the extent possible to the spiritual development of the young generation in accordance with the way of thinking of our people and in an understandable form. need Today, at a time when comprehensive reforms are being implemented in Uzbekistan, it is more important than ever to increase the responsibility of the individual to the society.